Hukum Produk Simpanan Serta Perjanjian-Perjanjian Yang Berkaitan Dengan Produk Simpanan - Dea Putri Gustianingsih; Irfan Ridha; Adyta Telianda; Alfani H. Mustofa; Ifthinatul Mupidah; Inayah Al-Inffah; Intan Rahmadina Putri H.; Andre Wirandi; Dicky Kurniawan; Abdullah Syani Alamsyah; Ahmad Sulaiman (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
The purpose of this investigation was toknowing the laws of deposit products contained in Islamic banks for example, savings, deposits, and current accounts. As well as to find out the contracts or agreements contained in the deposit product. This research uses a employs a qualitative methodology and is of the descriptive research kind. As well as The gathering of data technique is the literary literature technique. Data analysis involves collecting data by method of information collected from the literacy of various books, journals that have accurate references. The inquiry's conclusions show that the legislation of preserving products in Islamic banking is permissible asprovided that they are consistent with Islamic either legally or in compliance with the specifications of Islamic banks. What is meant by not contradicting Islamic law is using predetermined contracts such as wadi'ah (deposit) and mudharabah (profit sharing). With the law on deposit products and the contracts contained therein, we can see that there are differences regarding the requirements for Islamic banks and conventional banks.